Reshaping ophthalmology training after COVID-19 pandemic - Ferrara, Mariantonia; Romano, Vito; Steel, David H; Gupta, Rajen; Iovino, Claudio; van Dijk, Elon H C; Romano, Mario R (Eye (London), 2020)
The coronavirus disease 2019 (COVID-19) pandemic has had a significant impact on practical activities and didactic teaching of residents and fellows. This survey aimed to propose long-term changes for ophthalmology training based on the changes experienced by trainees and their perception of new training opportunities. An online survey was distributed to ophthalmology trainees in multiple countries. Descriptive statistics were used to analyse the data. A total of 504 analyzable responses were collected from 32 different countries. The current impact of COVID-19 pandemic was described as "severe" by most trainees (55.2%); however, the future perspective was more optimistic as demonstrated by the greater number of responses reporting a presumed "moderate" (37.3%), "mild" (14.1%) or "slight" (4.2%) long-term impact. The vast majority of trainees reported a decrease ≥50% of clinical activity (76.4%) and >75% of surgical activity (74.6%). Although an initial gap in didactic teaching has been experienced by many (55.4%), regular web-based teaching was reportedly attended by 67.7% of the respondents. A strong agreement was found regarding the worthwhile role of web-based case-presentations in clinical training (91.7%), web-based discussion of edited surgical videos (85.7%) and simulation-based practice (86.9%) in surgical training. This survey, focusing on trainees' perspective, strongly reinforces the need to promptly include new technology-based training tools, such as web-based teaching, virtual surgical simulators, and telementoring, in long-term reorganisation of ophthalmology training to ensure its continuity and effectiveness, which would remain available even in the face of another unpredictable crisis within the health system.